Improvement of the Nonparallel Helical Gear Drive Performance Using the Modified Asymmetric Teeth with Tip Relief - Mohammed Abdulaal Kadhim; Mohammad Qasim Abdulah (Journal of Engineering)
Overheating is a common issue in a nonparallel helical gearing system. The reason is the high friction, sliding velocity, and tangential force that occurs between meshed gear teeth. These factors can result in negative outcomes such as increased power loss, low gear efficiency, breakdown, and scuffing. Two types of non-parallel helical gears have been utilized to estimate the meshing heat fluxes of a pair of non-parallel gear systems. The scenario involves a design of standard helical teeth and a modified asymmetric non-parallel helical system. The asymmetric tool designe serves as a reference for preparing a modified asymmetric helical gear, which the CNC machine can then cut. The hybrid curve has been compounded from three parts (hypocycloid-involute-tip relief) on the loaded side and (hypocycloid-involute-epicycloid) on the unloaded side, using different pressure angles for each side. The non-parallel helical gear drive that has teeth modified asymmetrically is better than a standard non-parallel helical gear drive. The numerical results indicate the best enhancements in the maximum contact stress and tooth root stress percentages are about 12.253% and 8.91%, respectively. Adjusting the helical gear teeth surface improves the generated heat flux, resulting in an enhancement percentage of approximately 39.567%. The enhancement percentage of pitch deviation under different rotational speeds has been the best compared with the standard case under the same conditions and a high-speed range with high local temperatures reaching about 15% and is good at the low-speed range by 10%.